Human rights in the mining & metals industry : overview, management approach and issues. (International Council on Mining and Metals, 2009)
The overall objective of this publication is to provide an overview of the main challenges and dilemmas that companies in the mining and metals sector are often faced with. More specifically, management approaches that member companies have applied to dealing with human rights challenges are reviewed. The publication aims to outline the various elements of the Sustainable Development Framework relating to human rights, highlight key pressure points of relevance to business and human rights, as well as some relevant external tools and initiatives; and briefly document approaches to dealing with human rights issues adopted by a number of ICMM members in order to facilitate the spread of good practice. The main audience for the guidance is ICMM members and other interested companies in the mining industry.
Keywords: Mineral industries -- Management.; Mineral industries -- Employees.; Conflict management.; Industrial relations.; Mine management.; elektronické knihy; electronic books